Hypertension and Complete Denture Therapy - A Retrospective Study - Chithralekha B1 , Revathi Duraisamy2 , Madhulaxmi M3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A completely edentulous state is when the patient is in a state of complete tooth loss. In the current world,an increasing demand for complete denture prosthesis is also seen. The lifestyle, food habits etc are thoughtto be major factors that are influencing the oral health of the current generation. Marked evidence hasbeen cited between the relationship of various systemic diseases like diabetes and completely edentulousstate. Hypertension is the state of elevated blood pressure. An evident association between hypertensionand oral diseases has been established previously. The aim of our study was to find the association betweenhypertension and a completely edentulous state. The study was performed in a university setting, it reviewedpatient records and analysed the data of 86000 patients between June 2019 and March 2020. A total of about450 entries were selected. Of this after removing multiple entries a total of 372 patients data were obtained.The collected data were compiled and tabulated using Microsoft Excel, then reviewed and exported to SPSSfor performing statistical analysis. In the study a total of 5 parameters were considered, but only for oneparameter a statistically significant data was found, and this was the demographic profile of the completelyedentulous patients, p value was found to be 0.0052 (p =0.005) hence proving the data to be significant.For the rest of the parameters the study considered, a statistically significant data was not obtained, butthe data has remarkable clinical significance. In the study, completely edentulous male population were,56%, the female population represented 43%. 27% of the completely edentulous patients in the study werehypertensive and that is not a negligible count. Within the limitations of the study, it can be stated that thereis a relation between hypertension and a completely edentulous state.